Is the X-ray bright z = 5.5 quasar SRGE J170245.3+130104 a blazar?. Issue 3 (22nd December 2022) - An, Tao; Wang, Ailing; Liu, Yuanqi; Sotnikova, Yulia; Zhang, Yingkang; Aditya, J N H S; Jaiswal, Sumit; Khorunzhev, George; Lao, Baoqiang; Lin, Ruqiu; Mikhailov, Alexander; Mingaliev, Marat; et al.
ABSTRACT: Jets may have contributed to promoting the growth of seed black holes in the early Universe, and thus observations of radio-loud high-redshift quasars are crucial to understanding the growth and evolution of the early supermassive black holes. Here we report the radio properties of an X-ray bright z = 5.5 quasar, SRGE J170245.3+130104 (J1702+1301). Our high-resolution radio images reveal the radio counterpart at the optical position of J1702+1301, while another radio component is also detected at ∼23.5 arcsec to the south-west. Our analysis suggests that this south-west component is associated with a foreground galaxy at z ≈ 0.677, which is mixed with J1702+1301 in low-frequency low-resolution radio images. After removing the contamination from this foreground source, we recalculated the radio loudness of J1702+1301 to be R >1100, consistent with those of blazars. J1702+1301 exhibits a flat radio spectrum (α = −0.17 ± 0.05, S ∝ ν α ) between 0.15 and 5 GHz; above 5 GHz, it shows a rising spectrum shape, and the spectral index α ^8.2_4.7 appears to be correlated with the variation of the flux density: in burst states, α ^8.2_4.7 becomes larger. J1702+1301 displays distinct radio variability on time-scales from weeks to years in the source's rest frame. These radio properties, including high radio loudness, rising spectrum, and rapid variability, tend to support it as a blazar.